Language Use among Malaysian Bloggers - Mustapha, Ramlee; Mei, Lydia Wong Su (ASPENSI, 2012)
ABSTRACT: Blogs are now marking a new mode of communication, making impact on domains such as virtual formation of speech communities, knowledge-sharing, pedagogical implication as well as formation of virtual identity. It is estimated that more than three billion websites in the world today and more than 70 million are blogs. In Malaysia, it is estimated that half a million blogs existed. Language used by bloggers could reflect the unique pattern of discourse within the blogosphere where the combination of both monologue and dialogue in a space-bound, digital environment is observed. Some studies show that a strong sense of identity is seen within the literacy practices in blogosphere where bloggers tend to use code-switching and code mixing in their blogs. Thus, the purpose of this study was to examine the dynamics of English language use among top-ranked Malaysian bloggers from the perception of final-year TESL (Teaching English as Second Language) undergraduate students. The study reveals that there are various linguistic features found in blogs and also in the interaction with one another in meaning-making process.Â Several implications are discussed.KEY WORD: Blogs, communication, virtual identity, language use, code mixing, and TESL students in Malaysia.IKHTISAR: Blog merupakan mod komunikasi baru yang memberi impak kepada domain seperti komuniti maya, perkongsian maklumat, implikasi pedagogi, dan pembentukan jatidiri maya. Dianggarkan lebih dari tiga bilion laman web sekarang dan lebih dari 70 juta adalah blog. Dianggarkan setengah juta blog wujud di Malaysia. Bahasa yang digunakan oleh pemblog melambangkan keunikan pola dalam sfera blog dengan gabungan monolog dan dialog dalam persekitaran digital. Beberapa kajian mendapati identiti yang tersendiri dalam amalan literasi blog di mana pemblog mempunyai kecenderungan untuk menggunakan pertukaran kod dan pencampuran kod dalam blog mereka. Tujuan kajian ini untuk mengenalpasti dinamika penggunakan Bahasa Inggeris dalam blog oleh pemblog Malaysia dari perspektif pelajar tahun akhir dalam bidang TESL. Kajian ini mendapati beberapa ciri-ciri linguistik dalam blog dalam pembinaan makna hasil dari interaksi di antara pemblog dan pembaca blog.Â Beberapa implikasi dibincangkan.KATA KUNCI: Blog, komunikasi, jatidiri maya, pengunaan bahasa, percampuran kod, dan pelajar TESL di Malaysia.About the Authors: Prof. Dr. Ramlee Mustapha is a Dean and Professor at the Faculty of Technical and Vocational Education UPSI (Sultan Idris University of Education), 35900 Tanjong Malim, Perak Darul Ridzuan, Malaysia; and Lydia Wong Su Mei is an English Teacher at the SMK (State Secondary School) Datuk Haji Abdul Rahman Yakub in Malaysia. E-mail: drramlee@yahoo.comHow to cite this article? Mustapha, Ramlee & Lydia Wong Su Mei. (2012). âLanguage Use among Malaysian Bloggersâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.2(1) Juni, pp.109-132. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (April 27, 2012); Revised (May 17, 2012); and Published (June 15, 2012).